Nisin ZP, a Bacteriocin and Food Preservative, Inhibits Head and Neck Cancer Tumorigenesis and Prolongs Survival - Kamarajan, Pachiyappan (PLoS One, 2015)
The use of small antimicrobial peptides or bacteriocins, like nisin, to treat cancer is a new approach that holds great promise. Nisin exemplifies this new approach because it has been used safely in humans for many years as a food preservative, and recent laboratory studies support its anti-tumor potential in head and neck cancer. Previously, we showed that nisin (2.5%, low content) has antitumor potential in head and neck squamous cell carcinoma (HNSCC) in vitro and in vivo. The current studies explored a naturally occurring variant of nisin (nisin ZP; 95%, high content) for its antitumor effects in vitro and in vivo. Nisin ZP induced the greatest level of apoptosis in HNSCC cells compared to low content nisin. HNSCC cells treated with increasing concentrations of nisin ZP exhibited increasing levels of apoptosis and decreasing levels of cell proliferation, clonogenic capacity, and sphere formation. Nisin ZP induced apoptosis through a calpain-dependent pathway in HNSCC cells but not in human oral keratinocytes. Nisin ZP also induced apoptosis dose-dependently in human umbilical vein endothelial cells (HUVEC) with concomitant decreases in vascular sprout formation in vitro and reduced intratumoral microvessel density in vivo. Nisin ZP reduced tumorigenesis in vivo and long-term treatment with nisin ZP extended survival. In addition, nisin treated mice exhibited normal organ histology with no evidence of inflammation, fibrosis or necrosis. In summary, nisin ZP exhibits greater antitumor effects than low content nisin, and thus has the potential to serve as a novel therapeutic for HNSCC.